THE STUDY OF LITERARY PARADIGMS FROM TRADITIONAL TO POST-STRUCTURAL - Zakaria; Alifiah Pratiwi; Sultan (University of Kuningan, 2026)
Literary studies and criticism from the early period to the post-structural era has undergone a long journey, and likewise, literary scholars have different paradigms in responding to literature. The aim of this writing is to present literary paradigms in depicting the periods of literary development. This writing presents the period of literary development in literature studies for the interests and pedagogical purposes of the reader. The method is conducted by systematic literature review (SLR) procedure. The study finds three phases of paradigm interpretation. First phase, the traditional era to the post-colonial emphasized the importance of the aesthetic aspects of literature as a means of learning the art of writing, as a way to convey moral messages and social and cultural wisdom, to present heroic epics offered in fairy tales, legends, and myths that exist in society, and also emphasize the importance of the biography and background of the author. Second phase, literary paradigm initiated by structuralists and formalists need to literary works independently, the scholars begin to discuss the aspects of epistemology, ontology, and the axiology of literature, the structural elements of literature, and the system of literary text signs by promoting Saussure's ‘signifier/signified’. The third phase is post-strukturalists paradigm, the scholars continue to debate Saussure's ideas broadly, to promote the authority of the reader in literary interpretation.